Assembly Line Balancing using Best Bud Search - Nevins, Arthur J. (Management Science, 1972)
A general purpose heuristic program (which has been applied to deductive question-answering and theorem proving) has now been applied to the problem of balancing assembly lines. The results indicate that the program is quite effective in its role as an assembly line balancer.